(Micro)structure, thermal behavior and mechanical properties of ethylene–propylene–1-octadecene terpolymers from chain-walking polymerization of 1-octadecene. (12th March 2019) - Leone, Giuseppe; Canetti, Maurizio; Pierro, Ivana; Zanchin, Giorgia; De Rosa, Claudio; Ricci, Giovanni; Bertini, Fabio
Abstract: This paper reports the polymerization of 1-octadecene catalyzed by a series of α-diimine Ni(II) complex, with methyl ligand backbone and different substituents in the ortho and para aryl positions, in combination with Et2 AlCl. We obtained semicrystalline ethylene–propylene–1-octadecene terpolymers with high molecular weight and narrow molecular weight distribution. The formation of such terpolymers is due to the numerous combinations of insertion and chain-walking pathways. The effect of the type of ligand and monomer feedstock concentration on the activity, regioselectivity, polymers (micro)structure, and structure/properties is thoroughly investigated by NMR, DSC, WAXD and SAXS. The thermal behavior and the crystal structure of the polymers are strongly influenced by the level of incorporation of methyl and longer alkyl branches. The chain heterogeneity of the polymers is investigated by successive self-nucleation and annealing thermal fractionation evaluating the crystallizable sequence length, and the lamellar thickness. Graphical abstract: Image 1 Highlights: α-diimine Ni(II) complexes polymerize 1-octadecene to afford ethylene/propylene/1-octadecene terpolymers. The ligand and the monomer feed concentration affect the branching type and distribution. The thermal properties and crystallinity of terpolymers are influenced by microstructure. The lamellar size decreases with increasing the content of longer than methyl branches. The tensile tests of the terpolymers show yielding phenomena and plastic deformation.